2018
DOI: 10.1111/anae.14322
|View full text |Cite
|
Sign up to set email alerts
|

Neostigmine‐induced weakness: what are the facts?

Abstract: This editorial accompanies an article by Kent et al., Anaesthesia 2018; 73: 1079-89.'There is nothing more deceptive than an obvious fact. ' -Sir Arthur Ignatius Conan Doyle (May 1859-July 1930)In this issue of Anaesthesia, Kent et al. [1] report that administration of neostigmine 2.5 mg (mean (SD) dose 35 (6) lg.kg À1 ) plus glycopyrrolate 450 lg to a small number of healthy volunteers, in the absence of a previously administered non-depolarising neuromuscular blocker (NMB), resulted in manifestations of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Both approaches are inappropriate because the duration of action of muscle relaxants is highly variable among individuals (risk of residual neuromuscular blockade) and because unnecessary administration of neostigmine is potentially harmful. It has indeed been shown in adult volunteers that neostigmine administered when TOF ratio has recovered to 1.0 transiently increases upper airway collapsibility to the same extent as when muscular blockade had recovered to a TOF ratio of 0.5 and without altering the TOF ratio of the adductor pollicis muscle . Although the clinical relevance of this finding is a matter of controversy, any risk of decreasing the upper airway muscles activity should be avoided at a time when upper airway obstruction could occur, that is, when the tracheal tube is removed (see below): Neostigmine should therefore not be administered when no muscular blockade is still present.…”
Section: Preparing Extubationmentioning
confidence: 99%
“…Both approaches are inappropriate because the duration of action of muscle relaxants is highly variable among individuals (risk of residual neuromuscular blockade) and because unnecessary administration of neostigmine is potentially harmful. It has indeed been shown in adult volunteers that neostigmine administered when TOF ratio has recovered to 1.0 transiently increases upper airway collapsibility to the same extent as when muscular blockade had recovered to a TOF ratio of 0.5 and without altering the TOF ratio of the adductor pollicis muscle . Although the clinical relevance of this finding is a matter of controversy, any risk of decreasing the upper airway muscles activity should be avoided at a time when upper airway obstruction could occur, that is, when the tracheal tube is removed (see below): Neostigmine should therefore not be administered when no muscular blockade is still present.…”
Section: Preparing Extubationmentioning
confidence: 99%
“…Was this in response to hypoventilation and desaturation? Or a second dose of reversal due to residual neuromuscular block ? The authors’ results indicated that ‘lung‐protective ventilation’ was found to be protective against early hypoxia in this study but the definition (a plateau threshold of 16 cmH 2 O) is not consistent with previous definitions .…”
Section: Avoiding Desaturationmentioning
confidence: 99%
“…We would like to challenge Naguib and Kopman's editorial assertion that Kent et al. 's study on neostigmine‐induced weakness in awake volunteers ‘probably has little or no clinical relevance’.…”
mentioning
confidence: 92%